Pengaruh Media Pembelajaran Berbasis Digital terhadap Keterampilan Memahami Teks Bacaan pada Materi Pelajaran Bahasa Indonesia di SD - Bintang Wulandari; Al Ihwanah; Ines Tasya Jadidah (Universitas Muhammadiyah Magelang, 2026)
This research was motivated by low reading comprehension skills among third-grade students at SD Negeri 233 Palembang due to monotonous lecture methods and limited digital media use. The objective was to determine the effect of digital-based learning media on Indonesian language reading comprehension skills. Employing quantitative experimental method with true experimental design (posttest-only control group), the study involved a population of 49 third-grade students and a purposive sample of 49 students (Class III A: 25 experimental; Class III B: 24 control). Data collected via 5-item essay posttest were analyzed using Shapiro-Wilk normality test, Levene homogeneity test, and Mann-Whitney U test via SPSS 27. Results revealed experimental class mean score of 83.36 versus 60.6 for control class, with 88% experimental students achieving KKM 75 standard. Mann-Whitney U test (p=0.000) rejected the null hypothesis. It is concluded that digital learning media (YouTube videos, Wordwall) significantly enhance students' reading comprehension skills.